Improvement of the energy evaluation methodology of individual office building with dynamic energy grading system. (July 2020) - Liu, Jiangyan; Li, Kuining; Liu, Bin; Li, Guannan
Highlights: A systematic methodology is proposed to quantitative evaluate the energy of individual building. The energy evaluation method comprises both dynamic energy benchmarking and dynamic energy grading. The number of grades and their ranges of the dynamic energy grading system is determined by clustering analysis. Energy penalty of various faults could be well assessed by the proposed energy quantitative evaluation method. Abstract: The energy benchmarking has been recognized as an effective methodology for assessing the energy uses of buildings. The authors' previous study proposed both energy benchmarking and energy consumption grading (ECG) methods to quantify the energy of the individual office building. However, the previous energy evaluation method employed a fixed ECG system, which causing the energy uses of most situations included in the same grade. It is insufficient to reflect the individual differences of actual buildings. Therefore, this study proposes an improved dynamic energy grading system to overcome the limitations. First, the new ECG system is established based on the clustering analysis. Then, comparative analysis is conducted between the previous and improved ECG systems. Further, the building energy performance at various faulty conditions are evaluated by the improved ECG system to verify its reliability. Results show that the improved ECG system addressed the irrational evaluation process of the previous ECG system. Besides, the building energy penalties in various faulty cases could be quantitatively assessed by the improved ECG system. With the proposed method, the building owners can more accurately understand the real-time energy consumption level of the individual building and its energy conservation potential.